How the Baby Boomers' Retirement Wave Distorts Model-Based Output Gap Estimates - Maik Hendrik Wolters (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Hours per capita measures based on the private sector as usually included in the set of observables for estimating macroeconomic models are affected by low-frequent demographic trends and sectoral shifts that cannot be explained by standard models. Further, model-based output gap estimates are closely linked to the observable hours per capita series. Hence, hours per capita that are not measured in concordance with the model assumptions can distort output gap estimates. This paper shows that sectoral shifts in hours and the changing share of prime age individuals in the working-age population lead indeed to erroneous output gap dynamics. Regarding the aftermath of the global financial crisis model-based output gaps estimated using standard hours per capita series are persistently negative for the US economy. This is not caused by a permanently depressed economy, but by the retirement wave of baby boomers which lowers aggregate hours per capita. After adjusting hours for changes in the age composition to bring them in line with the model assumptions, the estimated output gap gradually closes in the years following the global financial crisis.
Keywords: J11; C54; E32; 330